FAKTOR PENENTU STOCK RETURN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Kresna Yoga Prasetyo; Yuli Chomsatu; Suhendro Suhendro (Universitas Sanata Dharma, 2022)
Stock Return is the result of profit or loss from an investment and becomes the driving motivation in the investment process. This study aims to obtain empirical evidence about the effect of Profitability, Liquidity and Firm Size on Stock Return of Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021. The population in this study are all Manufacturing Companies in the Consumer Goods Industry Sector listed on the IDX in 2020-2021. Sampling in this study using purposive sampling and 28 companies that meet the criteria. The data analysis technique used multiple linear regression analysis. The results of this study indicate that Profitability and Firm Size have an effect on Stock Return. Meanwhile, Liquidity has no effect on Stock Return Keywords: Stock Return, Profitability, Liquidity, Firm Size